Communication—Sol-Gel Synthesized Magnesium Vanadium Oxide, MgxV2O5 · nH2O: The Role of Structural Mg2+ on Battery Performance. Issue 9 (12th July 2016) - Yin, Jiefu; Pelliccione, Christopher J.; Lee, Shu Han; Takeuchi, Esther S.; Takeuchi, Kenneth J.; Marschilok, Amy C.
Abstract : Magnesium intercalated vanadium oxide xerogels, Mg0.1 V2 O5 · 2.35H2 O and Mg0.2 V2 O5 · 2.46H2 O were synthesized using an ion removal sol gel strategy. X-ray diffraction indicated lamellar ordering with turbostratic character. X-ray absorption spectroscopy indicated greater distortion of the vanadium-oxygen coordination environment in Mg0.2 V2 O5 · 2.46H2 O. Elemental analysis after cycling in Li + or Mg 2+ based electrolytes revealed the magnesium content was unchanged, indicating structural Mg 2+ are retained. The Mg0.1 V2 O5 · 2.35H2 O material displayed high voltage, energy density, and discharge/charge efficiency, indicating promise as a cathode material for future magnesium based batteries.